Baba Syrgiannes - Baba Saruca, Saltuk Et-Turki Or So Called Sari Saltik - Özgül, Vatan (Journal of Alevism-Bektashism Studies, 2013)
The fundamental sources used during the researches for Sarı Saltik are the legendary books like Saltikname and Haci Bektas Veli Velayetnamesi and also the chronicle written by Yazicizade Ali about The Anatolian Selcuks. However we can find the historical identity of Sari Saltik, by referring to the contemporary works. It is aimed to find the historical identity of Sari Saltik in a manner, by leaving the paradigms aside and make the readings such that we do not know anything about the subject, but referring to the contemporary works. As a result, Sari Saltik is found to be a Kuman/Kipcak origined, borned at Dest-i Kipcak and maybe lived in Anatolia for a short period of time. We can come across with Turkish onomastics pointing out Sari Saltik in the Greek chronicles, but with significant distortions, due to differing expressions at a different language writing habit. Hence the Greek Chronicles clearly states that the aforementioned character is a Kuman Turk, meaning that his name is also a Kuman-Turkish name. The date of born, place of birth, date of death and the place where Sarı Saltık had died is clarified in our article. Contrary to what is known and believed, his religious background seems to be mostly dominated by Karmati- İsmaili order, which is an obvious Alevi trend of Esoteric Islamic way, but may also be influenced by Haydari and/or Rufai orders.
Keywords: Sarı Saltik; Baba Saltik; Saltuk et-Turki; Sytzigan; Syrgiannes; Saronius; Baba Saruca; Dobrugia; Dest-i Kipcak (Kypcak Steep); Cumans; Kypcaks; Haydari; Rufai; Qarmati; Ismaili